The economics of education : a comprehensive overview - Bradley, Steve, 1957-; Green, Colin (Amsterdam : Elsevier, AP/Academic Press, an imprint of Elsevier, 2020)
The Economics of Education: A Comprehensive Overview, Second Edition, offers a comprehensive and current overview of the field of that is broadly accessible economists, researchers and students. This new edition revises the original 50 authoritative articles and adds Developed (US and European) and Developing Country perspectives, reflecting the differences in institutional structures that help to shape teacher labor markets and the effect of competition on student outcomes. --
Includes bibliographical references and index.
Buku bacaan asas prasiswazah Fakulti Ekonomi Pengurusan 2023/2024.
Keywords: Education -- Economic aspects -- Developing countries; Education -- Finance; Education -- Economic aspects